Estimate of the discard of ferrous and not ferrous metals - Da Silva, Nilza Regina [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Da Silva, Antonio Carlos Dalácqua; Leão, Alcides L. [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP] (My University, 2009)
It was believed that the impacts related to the humankind activities had repercussion only at local scope, and in some cases in the regional, and these problems could be easily decided. However, today it is common that the anthropic vision can be so extensive and complex that it is capable of generating a series of events not planned and, therefore, difficult to be managed. Among these events, it is distinguished that the crescent generation of solid residues is stimulated mainly by the consumption needs of a society that does not stop growing. The selective collection, although is not the only solution for the problem of solid waste, it promotes the habit of waste separation at the source. The data of materials: aluminum, copper and scrap metal, was collected at Association of Collectors of Paper Cardboard and Recyclable Materials of São Manuel, São Paulo, Brazil in the period of 2003 to 2007. This study has the objective to develop equations to esteem the amount of ferrous and non ferrous materials and aim the improvement of efficiency and densification of its productive chain. It was verified that the models found are fit to esteem the amount of ferrous and non ferrous materials, for this enterprises.
Keywords: Aluminum; Collect selective; Copper; Estimate; Metal